2017
DOI: 10.1016/j.ympev.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of extant starfish (Asteroidea: Echinodermata) including Xyloplax, based on comparative transcriptomics

Abstract: A B S T R A C TMulti-locus phylogenetic studies of echinoderms based on Sanger and RNA-seq technologies and the fossil record have provided evidence for the Asterozoa-Echinozoa hypothesis. This hypothesis posits a sister relationship between asterozoan classes (Asteroidea and Ophiuroidea) and a similar relationship between echinozoan classes (Echinoidea and Holothuroidea). Despite this consensus around Asterozoa-Echinozoa, phylogenetic relationships within the class Asteroidea (sea stars or starfish) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 55 publications
6
47
3
Order By: Relevance
“…Analysis of the genome/transcriptome of the crown‐of‐thorns starfish Acanthaster planci has revealed the presence of genes/transcripts encoding proteins that are orthologs of ArPPLNP1 and ArPPLNP2 (Smith et al, ). Furthermore, based on recent extensive molecular analysis of the phylogenetic relationships of extant Asteroidea (Linchangco et al, ), the occurrence of PPLNP1‐type (SMP‐type) and PPLNP2‐type proteins in A. rubens (order Forcipulatida) and in A. planci (order Valvatida) suggests that both of these PP/OK‐type precursors would have been present in the common ancestor of all extant starfish. Previous studies have shown that PPLN1‐type (SMP‐type) peptides act as muscle relaxants in P. pectinifera (order Valvatida and in A. rubens (order Forcipulatida) and therefore it seems likely, based on asteroid phylogeny (Linchangco et al, ), that PPLN1‐type peptides act as muscle relaxants in all extant starfish.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the genome/transcriptome of the crown‐of‐thorns starfish Acanthaster planci has revealed the presence of genes/transcripts encoding proteins that are orthologs of ArPPLNP1 and ArPPLNP2 (Smith et al, ). Furthermore, based on recent extensive molecular analysis of the phylogenetic relationships of extant Asteroidea (Linchangco et al, ), the occurrence of PPLNP1‐type (SMP‐type) and PPLNP2‐type proteins in A. rubens (order Forcipulatida) and in A. planci (order Valvatida) suggests that both of these PP/OK‐type precursors would have been present in the common ancestor of all extant starfish. Previous studies have shown that PPLN1‐type (SMP‐type) peptides act as muscle relaxants in P. pectinifera (order Valvatida and in A. rubens (order Forcipulatida) and therefore it seems likely, based on asteroid phylogeny (Linchangco et al, ), that PPLN1‐type peptides act as muscle relaxants in all extant starfish.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on recent extensive molecular analysis of the phylogenetic relationships of extant Asteroidea (Linchangco et al, ), the occurrence of PPLNP1‐type (SMP‐type) and PPLNP2‐type proteins in A. rubens (order Forcipulatida) and in A. planci (order Valvatida) suggests that both of these PP/OK‐type precursors would have been present in the common ancestor of all extant starfish. Previous studies have shown that PPLN1‐type (SMP‐type) peptides act as muscle relaxants in P. pectinifera (order Valvatida and in A. rubens (order Forcipulatida) and therefore it seems likely, based on asteroid phylogeny (Linchangco et al, ), that PPLN1‐type peptides act as muscle relaxants in all extant starfish. This study is the first to reveal the myorelaxant activity of PPLN2‐type peptides in a starfish species— A. rubens (order Forcipulatida).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we investigated the structural and chemical basis of temporary adhesion in the valvatid species Asterina gibbosa . The most recent molecular phylogeny of the Class Asteroidea supports a tree in which two main groups apparently diverged early in the evolution of sea stars [30]. According to this phylogeny, A. gibbosa and A. rubens could be considered as distantly-related species as they each belong to one of these two main sea star clades.…”
Section: Introductionmentioning
confidence: 99%